Review on Vishajanya Janapadodwamsa Vyadhi w.s.r. to Environmental Toxicity - pujar, Bhavani; Budihal, Shivakumar (International Research Journal of Ayurveda & Yoga, 2024)
Environmental toxicology is a multidisciplinary domain of science, which occupies an important niche, overlapping the field of toxicology. It focuses on humans and other living beings and therefore plays an important role in addressing public health challenges. With increasing numbers of environmental problems, there is a need for immediate health solutions. Environmental toxicity and its health hazards are not a new global issue; it has been in practice for 5,000 years. In olden days, kings, when they entered enemy kingdoms along with the military, faced the threat of being poisoned by entities like air, water, land, grass, and cattle feed. In present days, because of human activities, industries, pesticides, chemicals, and other unhealthy behaviors, the environment is getting poisoned and affecting the health of not only human beings but also the other living creatures of the earth and aquatic ecosystems. The present COVID-19 crisis is also a kind of environmental toxicity affecting the whole world. This paper is an attempt to review the health problems and methods of purification of such environmental particulates explained in classical texts and discuss the adaptation of these methods for challenging problems related to environmental toxicity in the present era.